1.Rozwiąz równiania:
a) 9m-2m+6=27
b)-13+27=-n+19+2n
c)3x+5=2x+12
d)4x-6=x+9
e)5n+12=9n-16
f)5x-x+6=-4+2x-8x

2.Rozwiąz równiania
a)3(x+2)=23
b)2(3a+7)+a=70
c)5(w+3)-63(w+1)=10
d)6(x-7)-2(x-4)=14
e)4x-3(x-2)=41
f)54=3(4x-2)
g)4-(2x+3)=7x-(2x+13)
h)4(x+3)+2(x-6)
i)-4(3t-20)=-1-11t
j)-3(2m+5)+7m=23-37
k)-3(4d+2)+5d=d-(9+4d)
l)-4(y-1)=8-(3y-8)-4y

1

Odpowiedzi

2010-03-29T14:45:29+02:00
1.
a)
9m-2m+6=27
7m=27-6
7m=21/:7
m=3
b)
-13+27=-n+19+2n
14-19=n
-5=n
c)
)3x+5=2x+12
3x-2x=12-5
x=7
d)
4x-6=x+9
4x-x=9+6
3x=15/:3
x=5
e)
5n+12=9n-16
5n-9n=-16-12
-4n=-28/:(-4)
n=7
f)
5x-x+6=-4+2x-8x
4x+6x=-4-6
10x=-10/:10
x=-1

2.
a)
3(x+2)=23
3x+6=23
3x=23-6
3x=17/:3
x=17/3
x=5 i 2/3
b)
2(3a+7)+a=70
6a+14+a=70
7a=-14+70
7a=56 /:7
a=8
c)
5(w+3)-63(w+1)=10
5w+15-63w-63=10
-58w=48+10
-58w=58 /:(-58)
w=-1
d)
6(x-7)-2(x-4)=14
6x-42-2x+8=14
4x=34+14
4x=48 /:4
x=12
e)
4x-3(x-2)=41
4x-3x+6=41
x=41-6
x=35
f)
54=3(4x-2)
54=12x-6
-12x=-6-54
-12x=-60/:(-12)
x=5
g)
4-(2x+3)=7x-(2x+13)
4-2x-3=7x-2x-13
-2x-5x=-13-1
-2x=-14/:(-2)
x=7
h)
4(x+3)+2(x-6)----????
i)
-4(3t-20)=-1-11t
-12t+80=-1-11t
-12t+11t=-1-80
-t=-81 /*(-1)
t=81
j)
-3(2m+5)+7m=23-37
-6m-15+7m=23-37
m=-14+15
m=1
k)
-3(4d+2)+5d=d-(9+4d)
-12d-6+5d=d-9-4d
-7d+3d=-9+6
-4d=-3/:(-4)
d=3/4
l)
-4(y-1)=8-(3y-8)-4y
-4y+4=8-3y+8-4y
-4y+7y=16-4
3y=12/:3
y=4